Contested Heritage in European Museums: Return, Transfer, Repatriation, or Restitution? - G. A. Nelaeva (Vestnik MGIMO-Universiteta, 2025)
Book review: Stahn C. Confronting Colonial Objects. History, Legality and Access to Culture. Oxford: Oxford University Press, 2023. 592 p.